SOCIAL MEDIA CONTENT AND RE-PURCHASHING BEHAVIOR: THE MEDIATION ROLE OF E-WOM - Novie, Muhafhidah (Magister Manajemen Universitas Islam Malang, 2023)
This research aims to determine the relationship between the role of e- WOM in mediating the relationship between social media content and re-purchasing behavior, while also analyzing the relationship between social media content and e-WOM, and the relationship between e-WOM and re-purchasing behavior. Research using a quantitative approach using partial least squares (PLS). The population in the study were consumers of Deliwafa Store which has branches in Surabaya, Sidoarjo, Gresik, and Malang. The sample in this study was determined using purposive sampling, with a total sample used of 172 respondents. The results of this study indicate that social media content has no significant effect on re-purchasing behavior, social media content has a significant effect on e-WOM, e-WOM has a significant effect on re-purchasing behavior, and e-WOM has a significant effect in mediating the relationship between social media content and re-purchasing behavior.